The Water Issue in Iran-Afghanistan Relations - Armen Israyelyan (Banber Arevelagitut'yan Instituti)
The problems with the Iranian-Afghan water issue are the result of the demarcation of the border between the two countries caused by external interference at different historical periods. Over the past 150 years, four agreements have been signed between Iran and Afghanistan on the use of water from border rivers, but they have never been fully implemented. The issue of water resources is a very sensitive issue for Iran and Afghanistan. Over the years, the emergence of complex environmental, agricultural, economic, social, legal, security, political and military factors has exacerbated the situation. Out of geopolitical interests, Great Britain and Russia divided the territories of Iran and Afghanistan into zones of influence in 1907, essentially depriving these countries of their sovereignty. In this situation, the settlement of border disputes between Iran and Afghanistan was entrusted to a third party, namely Great Britain, Turkey and the United States. Since the aforementioned countries were guided by their own interests when drawing the border between Iran and Afghanistan, as a result of the demarcation between the sides, it was not possible to find a solution to the water use of the Helmand River that would satisfy both Iran and Afghanistan.